2021
DOI: 10.1007/s10517-021-05349-3
|View full text |Cite
|
Sign up to set email alerts
|

Monooxygenase System and NO Metabolism in Liver Microsomes of Rats with Toxic Hepatitis and the Effect of Sesquiterpene Lactones

Abstract: We analyzed changes in activities of enzymes of phases I and II of xenobiotic biotransformation and parameters of NO metabolism in liver microsomes of rats with toxic CCl 4 -induced hepatitis after a 14-day course of sesquiterpene lactones from Artemisia leucodes (10 mg/kg). It was found that toxic hepatitis was associated with significant inhibition of NADPH-cytochrome c-reductase, benzo(a)pyrene hydroxylase, and NADPH-diaphorase, reduced cytochrome P-450 content, and enhanced induction of nitrate/nitrite red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A. Alahmari reported that furano-sesquiterpenes have a broad range of cytoprotective effects against various chemical or physical stimuli that induce cellular injury, where sesquiterpenes act as electron donors to break off the radical system via reaction with reactive oxygen species and then transform them into the most stable product (Tursunova et al, 2021;Yousefi-Manesh et al, 2021). Interestingly, this property contributed to the ability of AME to stimulate the biosynthesis of metabolites with thiol groups, which are known to protect cells from oxidative stress (Bone, 2003).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%
“…A. Alahmari reported that furano-sesquiterpenes have a broad range of cytoprotective effects against various chemical or physical stimuli that induce cellular injury, where sesquiterpenes act as electron donors to break off the radical system via reaction with reactive oxygen species and then transform them into the most stable product (Tursunova et al, 2021;Yousefi-Manesh et al, 2021). Interestingly, this property contributed to the ability of AME to stimulate the biosynthesis of metabolites with thiol groups, which are known to protect cells from oxidative stress (Bone, 2003).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%
“…The Curcumol SQ from Curcuma kwangsiensis (Zingibetaceae) inhibited the VEGF/AKT/eNOS signaling pathway, and reduced expression of NO, inhibiting liver angiogenesis and mediating anti-fibrotic effects in liver [66]. SQ lactones from Artemisia leucodes (Asteraceae) showed hepato-protective properties, stimulating changes in NO metabolism in the monooxygenase and NOergic systems in hepatocytes in animals with acute toxic hepatitis [115]. In addition, alantolactone, a SQ lactone from Inula helenium (Asteraceae), decreased the expression of COX-2, iNOS, MMPs, and a disintegrin and metalloproteinase with thrombospondin motif 5 induced by IL-1β in mouse chondrocytes in an osteoarthritis model [116].…”
Section: Production Of No In Inflammation Inflammatory Markers and It...mentioning
confidence: 99%